2010
DOI: 10.1590/s1519-69842010000200005
|View full text |Cite
|
Sign up to set email alerts
|

How many studies are necessary to compare niche-based models for geographic distributions? Inductive reasoning may fail at the end

Abstract: The use of ecological niche models (ENM) to generate potential geographic distributions of species has rapidly increased in ecology, conservation and evolutionary biology. Many methods are available and the most used are Maximum Entropy Method (MAXENT) and the Genetic Algorithm for Rule Set Production (GARP). Recent studies have shown that MAXENT perform better than GARP. Here we used the statistics methods of ROC -AUC (area under the Receiver Operating Characteristics curve) and bootstrap to evaluate the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
0
18
0
2
Order By: Relevance
“…Comparative analyses of the statistical performance of GARP and MAXENT are available (Kumar et al, 2009;Colombo and Joly, 2010;Oliveira et al, 2010;Terribile et al, 2010). The CLIMEX method has been mainly applied to evaluate the invasion potential of exotic organisms (Kriticos et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analyses of the statistical performance of GARP and MAXENT are available (Kumar et al, 2009;Colombo and Joly, 2010;Oliveira et al, 2010;Terribile et al, 2010). The CLIMEX method has been mainly applied to evaluate the invasion potential of exotic organisms (Kriticos et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated, the GARP model does not respond to coordinate spacing, and might perform better in predicting distributions from incomplete coordinate sets (Costa and Schlupp 2010). The greater predictive capability of GARP models has been reported in other studies (Terribile and Diniz-Filho 2010;Townsend Peterson et al 2007).…”
Section: Performance Of Modelsmentioning
confidence: 60%
“…These models have been developed and widely used to predict the likely distribution of introduced species based on climatic and edaphic constraints (Elith et al 2006;Guisan and Thuiller 2005). Recent work has also focused on assessing the underlying assumptions, inherent simplifications, critical limitations and the reliability of these modeling techniques (Rodda et al 2011;Sinclair et al 2010;Terribile and Diniz-Filho 2010). Maximum entropy (Maxent; Phillips et al 2006) and genetic algorithm for rule set production (GARP; Stockwell and Noble 1992), two of the most commonly used presence data-only niche-based modeling methods, have been used for predicting spatial distributions of various species at different scales (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are statistical tools to validate the ENMs (see Allouche et al, 2006), choosing a single model is difficult and risky; therefore, one solution is to combine models. Recently, although tests have been developed to understand the sources of uncertainty in ENSEMBLE (methods, scenarios and models of circulation) (Buisson et al, 2010;Déqué et al, 2012), publications have generally found that the methods generate greater uncertainty in the predictions (see Diniz-Filho et al, 2010;Terribile et al, 2010). In addition, it is possible to map the uncertainties in geographic space (Diniz-Filho et al, 2009).…”
Section: Discussionmentioning
confidence: 99%